Identitas Sosial Remaja Suku Mandar dalam Pappasang: Implikasi Bagi Penyusunan Bahan Bimbingan - Irawan, Andy Wahyu; Mappiare-AT, Andi; Muslihati, Muslihati (Jurnal Kajian Bimbingan dan Konseling, 2018)
Pappasang is a Mandar Tribe cultural product which contains advice. This advice has a characteristic describes the tribe identity of Mandar Tribe. This study aimed to examine the social identity of the Mandar Tribe adolescents in Pappasang as well as the foundation of guidance material. The qualitative study of gadamerian hermeneutics interpreted the social identity of Mandar Tribe adolescents in Pappasang. The findings showed the social identity are: empathy; remind each other; mutual help; solidarity; keep the disgrace on a secret; obedient; generous; democratic. Then, the social identity in Pappasang constructed to be material for guidance and counseling.